Assessing Stress Induced by Fluid Shifts and Reduced Cerebral Clearance during Robotic-Assisted Laparoscopic Radical Prostatectomy under Trendelenburg Positioning (UroTreND Study) - Peschke, Tobias; Feuerecker, Matthias; Siegl, Daniel; Schicktanz, Nathalie; Stief, Christian; Zu Eulenburg, Peter; Choukér, Alexander; Buchheim, Judith-Irina (Methods and protocols, 2024)
In addition to general anesthesia and mechanical ventilation, robotic-assisted laparoscopic radical prostatectomy (RALP) necessitates maintaining a capnoperitoneum and placing the patient in a pronounced downward tilt (Trendelenburg position). While the effects of the resulting fluid shift on the cardiovascular system seem to be modest and well tolerated, the effects on the brain and the blood–brain barrier have not been thoroughly investigated. Previous studies indicated that select patients showed an increase in the optic nerve sheath diameter (ONSD), detected by ultrasound during RALP, which suggests an elevation in intracranial pressure. We hypothesize that the intraoperative fluid shift results in endothelial dysfunction and reduced cerebral clearance, potentially leading to transient neuronal damage. This prospective, monocentric, non-randomized, controlled clinical trial will compare RALP to conventional open radical prostatectomy (control group) in a total of 50 subjects. The primary endpoint will be the perioperative concentration of neurofilament light chain (NfL) in blood using single-molecule array (SiMoA) as a measure for neuronal damage. As secondary endpoints, various other markers for endothelial function, inflammation, and neuronal damage as well as the ONSD will be assessed. Perioperative stress will be evaluated by questionnaires and stress hormone levels in saliva samples. Furthermore, the subjects will participate in functional tests to evaluate neurocognitive function. Each subject will be followed up until discharge. Conclusion: This trial aims to expand current knowledge as well as to develop strategies for improved monitoring and higher safety of patients undergoing RALP. The trial was registered with the German Clinical Trials Register DRKS00031041 on 11 January 2023.